A Diversity-based Selfish Node Detection Algorithm for Socially Aware Networking - Xiao, Nan; Xinyi, Rang; Xiong, Zenggang; Xu, Fang; Zhang, Xuemin; Xu, Qiong; Zhao, Xiaochao; Ye, Conghuan (Journal of signal processing systems, 2021)
Because mobile devices only have the limited resource in socially aware networking, some network nodes are unwilling to sacrifice their resource to forward messages to others for free, thus forming selfish nodes. However selfish nodes will cause dropping in the message delivery rate and affect the network performance, so this paper has proposed a diversity-based selfish node detection algorithm (DSNDA). Firstly, it mainly applies the node forwarding willingness mechanism to detect whether the node is selfish. If the node has the inadequate resource, that is, it cannot forward any messages for others; then it will be selfish. If the node’s resource is enough and the node has forwarded messages to other nodes, it indicates that the node is not selfish. Otherwise, DSNDA algorithm will use reputation mechanism to check the node further. If the node has broken faith, it indicates that the node is selfish. On the contrary the message confirmation mechanism will be employed to make the final check on the node. If a message does not be received or discarded after the node’s receiving it, which proves that it has selfish behaviour. If not, the node is normal. It can be proved by the simulation experiment and results that the DSNDA algorithm has significantly improved the delivery rate of messages, comparing with other algorithms. At the same time, reducing the network delay, thus verifying the feasibility of DSNDA.